PELAYANAN SOSIAL KARITATIF POSKO “OMNIA IN CARITATE” KEUSKUPAN RUTENG KEPADA KELOMPOK RENTAN PADA MASA PANDEMI COVID-19 DI MANGGARAI RAYA - MARIANUS MANTOVANNY TAPUNG; MAX REGUS; MARSEL R. PAYONG; MARIANUS S. JELAHUT (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2020)
Abstract. The elderly, people with disabilities, people with HIV/AIDS, and people with mental disorders in vulnerable groups during the Covid-19 pandemic. This group must be given special attention because they are susceptible to Corona virus. The church as a social humanitarian institution is very concerned to pay attention to this group by doing charitable social services. This charitable social service aims to restore the physical and psychological state of this vulnerable group from the bad situation caused by the emergence of this Corona outbreak. These charitable social service activities are carried out using a combination of social work and social analysis methods. The impact of this activity is the recovery of physiological and psychological conditions of vulnerable groups. They were finally allowed to undergo this pandemic and new normal without any worries. Charitable social services have helped to make this group aware of their hygiene awareness in maintaining the condition of their bodies during this pandemic and in the future. The presence of the OiC Command Post in charitable social service activities in the form of providing social assistance in the form of food, vitamins and masks is enough to help vulnerable groups in meeting their nutritional needs during this pandemic. Adequate nutritional intake will greatly help maintain immunity and physical stamina, sustain economic needs, and maintain a healthy body. This charitable social service activity also had an impact on recognizing the existence of the Catholic Church as a religious social institution that not only offered heavenly (eschatological) salvation, but was also able to proclaim the real worldly salvation, now and here. Abstrak. Kaum lanjut usia/jompo, difabel, penderita HIV/AIDS, dan kaum yang mengalami gangguan mental termasuk kelompok rentan pada masa pandemi Covid-19. Kelompok ini mesti diperhatikan secara khusus karena rentan terpapar virus Corona. Gereja sebagai lembaga sosial kemanusiaan sangat berkepentingan untuk memperhatikan kelompok ini dengan melakukan pelayanan sosial karitatif. Pelayanan sosial karitatif ini bertujuan untuk memulihkan keadaan fisik dan psikis kelompok rentan ini dari situasi buruk akibat munculnya wabah Corona ini. Kegiatan pelayanan sosial karitatif ini dijalankan dengan menggunakan metode gabungan antara pekerjaan sosial dan analisis sosial. Dampak dari kegiatan ini adalah pulihnya keadaan fisiologis dan dan psikologis kelompok rentan. Mereka akhirnya boleh menjalani masa pandemi dan new normal ini tanpa rasa khawatir dan cemas. Pelayanan sosial karitatif telah turut menyadarkan kelompok ini agar tetap memiliki kesadaran higienik dalam memelihara dan menjaga kondisi tubuhnya selama masa pandemi ini dan masa-masa yang akan datang. Kehadiran tim posko OiC dalam kegiatan pelayanan sosial karitatif dalam bentuk pemberian bantuan sosial berupa sembako, vitamin dan masker cukup membantu kelompok rentan dalam memenuhi kebutuhan asupan gizi selama masa pandemi ini. Asupan gizi yang cukup akan sangat membantu mempertahankan imunitas dan stamina fisik, kelangsungan kebutuhan ekonomi, serta menjaga kesehatan tubuh. Kegiatan pelayanan sosial karitatif ini juga berdampak pada pengakuan terhadap eksistensi Gereja Katolik sebagai lembaga sosial religius yang tidak saja menawarkan keselamatan surgawi (eskatologis), tetapi juga mampu mewartakan secara nyata keselamatan duniawi, sekarang dan di sini.